Healthcare providers and IT-enabled organisational processes: the case of the Azienda Ospedaliera Universitaria Integrata of Verona. (28th January 2015) - Zardini, Alessandro; Rossignoli, Cecilia; Suppa, Armando; Ricciardi, Francesca; Benetollo, Pier Paolo
The use of information and communication technology (ICT) has become a primary lever of national and international public administration reform (Moon, 2002). The adoption and use of ICT by public organisations to facilitate the administration and delivery of citizen services is defined by the literature as 'e-government' (Grönlund, 2004a). An IT-enabled public administration and e-government are the pillars of the reforms launched by the more industrialised countries and this has led the Italian Government to assign priority to electronic healthcare (Bergamaschi et al., 2006), and in particular, to the creation of the electronic health record (longitudinal) or 'EHR'. This study investigates the implementation of a core element of the EHR, electronic medical records (EMRs), by the Azienda Ospedaliera Universitaria Integrata (Integrated NHS-University Hospital) of Verona, the deployment of which is expected to spur internal efficiency and pave the way for the development of the longitudinal EHR of the future. It then analyses the organisational impacts of EMRs on the healthcare provider's structure.